The surrender tree : poems of Cuba's struggle for freedom - Engle, Margarita (New York : Henry Holt, 2008)
A collection of poems in which Rosa, a healer, describes her experiences trying to help Cuban peasants who have been forced to leave their farms and villages in 1896 and given eight days to find their way to "reconcentration camps" or be killed.
Includes bibliographical references (p. 167-168).
Newbery Medal/Honor.
Wilson's Junior High School.
Wilson's Senior High School.
Booklist starred, March 2008.
Bulletin (Center for Children's books), May 2008.
Keywords: Children's poetry, American; American poetry; American poetry; Cuba -- History -- 1810-1899 -- Juvenile poetry; Cuba -- History -- 1810-1899 -- Poetry; Cuba -- History -- Poetry